AI-as-Historian. - Sternfeld, Joshua (American Historical Review, 2023)
This article investigates the concept of utilizing artificial intelligence (AI) in the field of history. First the article details the process of the historical method which involves selecting evidence, synthesizing evidence, and then contextualizing and interpreting evidence. Next AI system training is explored starting with training on datasets and testing, data synthesis, and back propagation. Along the way of detailing these processes they are compared and contrasted to each other.